Analisis Faktor Yang Mempengaruhi Kompetensi Profesional Guru Sekolah Dasar - Iis Indah Kurniasih; Suriswo Suriswo; Hanung Sudibyo (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
This study provides comprehensive explanations and information about the factors that influence the professional competence of elementary school teachers. The method used was a Systematic Literature Review (SLR) of five empirical articles published between 2020 and 2026. The five articles were selected because they met the inclusion and exclusion criteria used in the article requirements. The analysis process included article selection, data extraction, and thematic coding. Thematic coding was carried out using open coding, axial coding, and selective coding. The synthesis results showed that the professional competence of elementary school teachers is influenced by five main factors, namely principal leadership, continuous professional development, a collaborative and reflective school culture, academic supervision, and the implementation of curriculum and learning policies. These findings emphasize that efforts to improve teachers' professional competence must be carried out holistically and require the support of a sustainable school ecosystem to improve the quality of learning.